Risk factors and prognostic impact of venous thromboembolism in Asian patients with non-small cell lung cancer - Lee, Yun-Gyoo; Kim, Inho; Lee, Eunyoung; Bang, Soo-Mee; Kang, Chang Hyun; Kim, Young Tae; Kim, Hak Jae; Wu, Hong-Gyun; Kim, Young Whan; Kim, Tae Min; Lee, Keun-Wook; Lee, Se-Hoon; Kim, Dong-Wan; Heo, Dae Seog (Thrombosis and Haemostasis, 2014)
Although the overall risk of venous thromboembolism (VTE) is high in patients with non-small cell lung cancer (NSCLC), risk identification is limited. The goal of this study was to estimate the incidence, risk factors and prognostic implications of VTE, and to evaluate a genetic link between oncogenes and the risk of VTE in Asian patients with NSCLC. A total of 1,998 consecutive patients with NSCLC were enrolled and analysed retrospectively. Since the effects of therapeutics on VTE development were modified by stage, stratified analyses were performed. When comparing overall survival in terms of VTE development, a propensity score-matching method was adopted to minimise potential confounding. The six-month and two-year cumulative incidences of VTE were 4.2% and 6.4%, respectively. The risk of VTE increased 2.45-fold with each advancing stage in NSCLC (p<0.001). The independent predictors of VTE were advanced age, pneumonectomy and palliative radiotherapy in localised NSCLC and ineligibility for surgery and palliative radiotherapy in locally advanced NSCLC. Adenocarcinoma histology (vs squamous cell) and former/current smoking status were significant predictors of VTE in metastatic NSCLC. A significant association between VTE and decreased survival was observed only among patients with localised NSCLC. EGFR mutations (p=0.170) and ALK rearrangements (p=0.159) were not associated with VTE development in lung adenocarcinoma. In conclusion, the two-year cumulative incidence of VTE is 6.4% in Asian patient with NSCLC. The significant predictors of VTE are different across stages of NSCLC. The prognostic impact of VTE on poor survival was limited to localised NSCLC.
Keywords: Venous thromboembolism; non-small cell lung carcinoma; epidermal growth factor receptor; risk factor; prognosis